Happiness economics - Ada Ferrer-i-Carbonell (SERIEs - Journal of the Spanish Economic Association, 2013)
There is enough evidence to be confident that individuals are able and willing to provide a meaningful answer when asked to value on a finite scale their satisfaction with their own lives, a question that psychologists have long and often posed to respondents of large questionnaires. Without taking its limitations and criticisms too lightly, some economists have been using thismeasure of self-reported satisfaction as a proxy for utility so as to contribute to a better understanding of individuals' tastes and hopefully behavior. By means of satisfaction questions we can elicit information on individual likes and dislikes over a large set of relevant issues, such as income, working status and job amenities, the risk of becoming unemployed, inflation, and health status. This information can be used to evaluate existing ideas from a new perspective, understand individual behavior, evaluate and design public policies, study poverty and inequality, and develop a preference based valuation method. In this article I first critically assess the pros and cons of using satisfaction variables, and then discuss its main applications.
Keywords: D31; I1; I3; 330; happiness economics; preferences; subjective well-being; welfare